2015
DOI: 10.1515/pesd-2015-0030
|View full text |Cite
|
Sign up to set email alerts
|

Flood Analysis Using Hydrological Modeling. Case Study – The Flood In The Upper Catchment Of River Geru, Galaţi County, Romania

Abstract: This paper analyzes the flood that occurred between 11th and 13th of September 2013 in the upper catchment of the river Geru. The flood was simulated using the program Mike by DHI with the Unitary Hydrograph Method. As input data, we used the precipitation measured at the Automated Hydrological Sensor Station Cudalbi and radar precipitations. We analyzed the importance of accuracy for input data on the simulation results and the direct influence of setting the proper time steps in achieving the simulated disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Such differences can have a major impact on future runoff predictions which is the reason why it is prudent to not only rely on one method or even model. Balan et al, (2016) observed that the application of the SCS Generalised method yielded a hydrograph with four peaks, with a 26.5-hour difference in peak flow occurrence. The first peak was underestimated compared to the maximum recorded discharge, while the second one, which was the highest peak flow, overpredicted the measured value by 1.67%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such differences can have a major impact on future runoff predictions which is the reason why it is prudent to not only rely on one method or even model. Balan et al, (2016) observed that the application of the SCS Generalised method yielded a hydrograph with four peaks, with a 26.5-hour difference in peak flow occurrence. The first peak was underestimated compared to the maximum recorded discharge, while the second one, which was the highest peak flow, overpredicted the measured value by 1.67%.…”
Section: Discussionmentioning
confidence: 99%
“…The losses to infiltration, surface storage and evaporation are expressed as proportional losses (the rational method), as fixed initial and constant losses, by the curve number (CN) method or by the SCS (Soil Conservation Service) Generalized one (DHI, 2017a). Balan et al, (2016) conducted a runoff simulation study in the upper catchment of river Geru, using the Mike 11 modelling system with NAM and UHM modules, based on the rainfall event recorded on 11-13 September 2013. The four methods available in the UHM module were applied successively and the results were finally compared with those of the NAM module.…”
Section: Introductionmentioning
confidence: 99%